Tinjauan Hukum Pidana Islam dan Pasal 44 Kitab Undang-undang Hukum Pidana Terhadap Pelaku Pencurian Pengidap Kleptomania (Studi Putusan Nomor : 32/Pid.B/2018/PN.Kpg) - Fikri, Ikhwan; Fathimah, Ema; Tiara, Bunga Putri (Muqaranah, 2023)
One of the cases that needs to be anticipated and followed up in criminal cases is theft, which often disturbs the public. An example is the case of a criminal act of theft committed by a kleptomania sufferer by a housewife who lives in Kupang City in 2017. This research discusses the analysis of jinayah fiqh or Islamic criminal law and positive law on the application of criminal sanctions for theft based on KUPANG District Court Decision Number 32/Pid.B/2018/PN Kpg. The research method used by researchers is a normative research method which is carried out by examining laws and regulations that are directly related to the crime of theft. The results of the research that have been studied by researchers are that according to article 44 paragraph of the Criminal Code concerning the responsibility of perpetrators of criminal acts of theft who experience mental disabilities such as sufferers of kleptomania, the judge has the authority to decide on an order and send the perpetrator of the crime to a mental hospital for the longest possible time. one year, while the crime of theft by a person suffering from kleptomania according to Islamic law is not subject to a had sentence but rather a ta'zir punishment as ta'dib or teaching in the form of a rehabilitation sentence and a fine which is accountable to the victim.